The annual register : world events 2007 - Lewis, D. S.; Slater, Wendy, 1967- (Annual register, 2008)
Provides a complete and detailed chronicle of historical events from 1758 to the current day. Includes world politics to society weddings, from the latest scientific discoveries to the weather, from the year's best-selling novels to obituaries of authors and other public figures. A new volume is published each year describing the past year's events.